-
Notifications
You must be signed in to change notification settings - Fork 1
/
M-143-PowerRule.tex
219 lines (130 loc) · 5.72 KB
/
M-143-PowerRule.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
\documentclass[10pt]{article}
% The following command leaves more space between lines. That's great
% when correcting drafts. When you comment it out, however, the
% output looks much nicer.
%
\linespread{1.0}
\usepackage{amsmath}
\usepackage{amssymb}
\usepackage{graphicx}
\usepackage{epsfig}
\usepackage{latexsym}
\usepackage{amsthm}
\usepackage{mathrsfs}
\usepackage{multicol}
\usepackage[colorlinks,citecolor=blue]{hyperref}
\usepackage[latin1]{inputenc}
\usepackage{tikz-cd}
\usepackage{pgfplots}
%\usepackage{3dplot}
\usetikzlibrary{matrix,arrows,decorations.pathmorphing}
\usepackage[scale=0.8]{geometry}
%\usepackage{umoline}\setlength{\UnderlineDepth}{1pt}
%\usepackage[linktocpage=true]{hyperref}
\input xy
\xyoption{all}
%\addtolength{\hoffset}{-.5in}
%\addtolength{\textwidth}{1in}
%\setlength{\parindent}{.5in}
%\setlength{\textheight}{9.5in} \setlength{\topmargin}{-2cm}
\pagestyle{myheadings}\parindent 0em
\usepackage[latin1]{inputenc}
%------------------copy and posted code from the internets-------------
%\numberwithin{equation}{section} % comment out when neccessary
\newtheorem{theorem}[equation]{Theorem}
\newtheorem{lemma}[equation]{Lemma}
\newtheorem{proposition}[equation]{Proposition}
\newtheorem{corollary}[equation]{Corollary}
\theoremstyle{definition}
\newtheorem{definition}[equation]{Definition}
\newtheorem{example}[equation]{Example}
\newtheorem{remark}[equation]{Remark}
\newtheorem{problem}[equation]{Problem}
\newcommand{\R}[1]{\mathbb{R}^{#1}}
\newcommand{\C}[1]{\mathbb{C}^{#1}}
\newcommand{\Z}[1]{\mathbb{Z}^{#1}}
\newcommand{\K}[1]{\mathbb{K}^{#1}}
\newcommand{\embed}[0]{\hookrightarrow}
\newcommand{\TT}[4]{\begin{tabular}{| c | c |}\hline $#1$ & $#2$ \\ \hline $#3$ & $#4$ \\ \hline\end{tabular}} %goddamn it
\newcommand{\partd}[2]{\frac{\partial #1}{\partial #2}}
\newcommand{\limit}[2]{\displaystyle{ \lim_{#1 \to #2}}}
\newcommand{\vectornorm}[1]{\left|\left|#1\right|\right|}
\newcommand{\Ker}[0]{\text{\textnormal{Ker}}}
\newcommand{\Hom}[0]{\text{\textnormal{Hom}}}
\newcommand{\circled}[1]{\tikz[baseline=(char.base)]{
\node[shape=circle,draw,inner sep=2pt] (char) {#1};}}
\newcommand{\T}{\rotatebox[origin=c]{180}{$\scriptscriptstyle \perp $}}
\newcommand{\x}{\textbf{x}}
\newcommand{\y}{\textbf{y}}
\newcommand{\supp}{\text{\textnormal{supp}}}
\newcommand{\csupp}{\text{\textnormal{cosupp}}}
\newcommand{\found}{\text{\textnormal{found}}}
\newcommand{\roof}{\text{\textnormal{roof}}}
\newcommand{\bcup}{\displaystyle\bigcup}
\newcommand{\bcap}{\displaystyle\bigcap}
\newcommand{\dsum}{\displaystyle\sum}
\newcommand{\dint}{\displaystyle\int}
\begin{document}
%
{\bf Name:} \hrulefill\hrulefill\hrulefill\\
{\bf M143} \qquad \qquad \\
{\bf Basic and Power rule of Derivatives}\\ %(look familiar??)\\
%Show all work for full/partial credit.
%---------------- End of the document ---------------
\section{Basic rules of the derivative}
At this point we probably are, or should be, sick of computing limits like: $$\limit{h}{0}\frac{2(x+h)^3-4(x+h)-(2x^3-4x)}{h}.$$ This is technically the derivative of $f(x)=2x^3-4x$. But there's 2 sides to mathematics, theres the formal definition, and then we should leverage our knowledge and try to find shortcuts to some of these things. So let's figure some of these things out.\\
Given functions $f(x), g(x)$ and constants $a,b$ we have: $$\frac{d}{dx}[a(f)x)+bg(x)]=af'(x)+bg'(x).$$ How do we know that? Well:
\begin{eqnarray*}
\frac{d}{dx}[a(f)x)+bg(x)]&=&\limit{h}{0}\frac{af(x+h)+bg(x+h)-(af(x)-bg(x))}{h}\\
&=&\limit{h}{0}\frac{af(x+h)-af(x)}{h}+\limit{h}{0}\frac{bg(x+h)-bg(x)}{h}\\
&=&a\limit{h}{0}\frac{f(x+h)-f(x)}{h}+b\limit{h}{0}\frac{g(x+h)-g(x)}{h}\\
&=&af'(x)+bg'(x).
\end{eqnarray*}
\section{Power Rule}
We may have noticed a pattern with derivatives. But to illustrate it explicitly:
\begin{itemize}
\item The derivative of $f(x)=x^0$, it's the derivative of the constant function $f(x)=1$, and since its a horizontal line, it never has any slope and $f'(x)=0$.
\item The derivative of $f(x)=x^1$, it's the derivative of the line $f(x)=x$ which always has slope 1, so $f'(x)=1$.
\item The derivative of $f(x)=x^2$ is:
\begin{eqnarray*}
f(x)&=&\limit{h}{0}\frac{f(x+h)-f(x)}{h}\\
&=&\limit{h}{0} \frac{(x+h)^2-x^2}{h}\\
&=&\limit{h}{0} \frac{x^2+2xh+h^2-x^2}{h}\\
&=&\limit{h}{0} \frac{(2x+h)h}{h}\\
&=&\limit{h}{0} 2x+h=2x.\\
\end{eqnarray*}
\item The derivative of $f(x)=x^3$ is:
\begin{eqnarray*}
f(x)&=&\limit{h}{0}\frac{f(x+h)-f(x)}{h}\\
&=&\limit{h}{0} \frac{(x+h)^3-x^3}{h}\\
&=&\limit{h}{0} \frac{x^3+3x^2h+3xh^2+h^3-x^3}{h}\\
&=&\limit{h}{0} \frac{(3x^2+3xh+h^2)h}{h}\\
&=&\limit{h}{0} 3x^2+3xh+h^2=3x^2.\\
\end{eqnarray*}
\end{itemize}
To generalize this, we have a rule of differentiation called the {\bf power rule} which goes: $\frac{d}{dx}[x^n]=nx^{n-1}$. \\
To verify:
\begin{itemize}
\item $\frac{d}{dx}[x^0]=0x^{0-1}=0$.
\item $\frac{d}{dx}[x^1]=1x^{1-1}=1$.
\item $\frac{d}{dx}[x^2]=2x^{2-1}=2x$.
\item $\frac{d}{dx}[x^3]=3x^{3-1}=3x^2$.
\end{itemize}
What's fascinating is that this rule applies to {\bf all} powers, not just integer powers.
\section{Examples}
We can combine these rules to find the derivatives of some basic functions. So consider the derivative of $f(x)=x^4-2x^2+7x-3$. It would be:
\begin{eqnarray*}
f'(x)&=&\frac{d}{dx}[x^4-2x^2+7x-3]\\
&=&\frac{d}{dx}[x^4-2x^2+7x^1-3x^0]\\
&=&4x^3-2(2x^1)+7(1x^0)-3(0x^{-1})\\
&=&12x^3-4x+7.
\end{eqnarray*}
Whereas the derivative of $g(x)=\sqrt{4x}+\frac{3}{x}-\frac{2}{x^2}$ would be:
\begin{eqnarray*}
g'(x)&=&\frac{d}{dx}[\sqrt{4x}+\frac{3}{x}-\frac{2}{x^2}]\\
&=&\frac{d}{dx}[2x^{1/2}+3x^{-1}-2x^{-2}]\\
&=&2(1/2)x^{-1/2}+3(-1x^{-2})-2(2x^{-3})\\
&=&x^{-1/2}-3x^{-2}+4x^{-3}\\
&=&\frac{1}{\sqrt{x}}-\frac{3}{x^2}+\frac{4}{x^3}.
\end{eqnarray*}
\end{document}